The Mediating Role of Hope and Loneliness in the Relationship Between Meaningful Life and Psychological Resilience in the Covid-19 Pandemic During - Batmaz, Hasan; Türk, Nuri; Doğrusever, Caner (Muş Alparslan Üniversitesi, 2021)
The pandemic has also revealed the quarantine processes. Therefore, individuals'psychological resilience and loneliness are also affected. As a result, individuals have made efforts to seek hope and meaningful life paths in this life. In this study, the role of hope and meaningful life in the relationship between the loneliness levels of university students and their psychological resilience was examined. The study was carried out on a total of 307 university students, 208 (68%) female and 99 (32%) male. The easy-to-reach sampling method was used in the study. According to the results of the research, significant relationships were found between loneliness, resilience, hope and meaningful life. Preloading results showed that hope and meaningful life had a partial mediating effect on the relationship between loneliness and resilience.

The pandemic has also revealed the quarantine processes. Therefore, individuals'psychological resilience and loneliness are also affected. As a result, individuals have made efforts to seek hope and meaningful life paths in this life. In this study, the role of hope and meaningful life in the relationship between the loneliness levels of university students and their psychological resilience was examined. The study was carried out on a total of 307 university students, 208 (68%) female and 99 (32%) male. The easy-to-reach sampling method was used in the study. According to the results of the research, significant relationships were found between loneliness, resilience, hope and meaningful life. Preloading results showed that hope and meaningful life had a partial mediating effect on the relationship between loneliness and resilience.
Covid-19 Salgın Sürecinde Anlamlı Yaşam ve Yılmazlık Arasındaki İlişkide Umut ve Yalnızlığın Aracı Rolü
anemon
Keywords: Covid-19; Anlamlı Yaşam; Yılmazlık; Yalnızlık; Umut; Covid-19; Meaningful Life; Psychological Resilience; Hope; Loneliness